A Resonator Noise Reduction Solution for a Centrifugal Gas Compressor - Deaconu, Marius; Cican, Grigore; Dragasanu, Luminita; Cristea, Laurentiu (Engineering, Technology & Applied Science Research, 2024)
The purpose of this work is to reduce the noise generated by a compressor that conveys methane gas. After certain measurements were conducted a high level of noise was observed in the 2000-3000 Hz range, therefore a solution for noise reduction at the source is addressed and presented in this paper. The research method is based on designing resonators to be applied on the stator of a centrifugal compressor used in a natural gas distribution station. First, the calculations are made on resonators with air as the working fluid and then are validated through real measurements in a Kundt tube. After validation, the working fluid is changed with gas, calculations are made once again, and acoustic simulations are performed. To facilitate acoustic simulations and reduce computational time, a simplified stator geometry was employed. This simplified model encompassed the region starting from the rotor’s gas exit, where the resonators were deployed. The purpose of the acoustic simulation was to validate the frequency range influenced by the resonators and to estimate the overall noise reduction. Depending on the operating regime of the compressor, the rotor fundamental can vary within the frequency domain of 2000 – 3000 Hz. This broadband domain requires the usage of several resonators with different resonant frequencies. The proposed solution obtained an average value of attenuation, excluding the peaks of the attenuation, in the frequency domain of 2000 - 3000 Hz, of 9 dBA. If the fundamental frequency coincides with a resonance of the resonator, higher attenuation can occur. Also, fundamental attenuation can lead to attenuation of the harmonics.